The Problem Solving Ability of Students in the Cooperative Learning Simulation of Kancing Gemerincing Technique with Ethnomathematics Nuances Reviewed by the Cognitive Mode - Mukeriyanto, Mukeriyanto; Mastur, Zaenuri; Mulyono, Mulyono (Unnes Journal of Mathematics Education Research, 2020)
This study aims to (1) test the effectiveness of the Modeling of the Kancing Gemerincing Learning technique with ethnomathematics nuances in improving students’ problem solving abilities; and (2) finding students’ problem solving ability models in terms of the cognitive mode that is taught with the cooperative learning simulation of the ethnomathematics Kancing Gemerincing technique. The method used is a combination method with a sequential explanatory research design. The study population was students of class VIII 1st Public Middle School of Gemawang, Temanggung. The selected classes chosen by using cluster random sampling method are, class VIIID as the experimental class and VIIIA as the control class. The technique used in quantitative data collection is by testing the problem solving skills and qualitative data collection is obtained by doing documentations, questionnaires, and interviews. Testing data used are completeness test, t test, and paired t test. The results showed that the cooperative learning of the Kancing Gemerincing technique with ethno-mathematics nuances was effective in improving students’ mathematical problem solving abilities. The problem solving ability of independent field students is able to build new knowledge with other fields, be able to apply different strategies in solving problems, and be able to reflect mathematical problem solving processes. Whereas, the problem solving ability of field dependent students is able to build new knowledge with other fields, but has yet been able to apply different strategies in solving problems and reflecting mathematical problem solving processes.